Predictors of good outcome in upper gastrointestinal bleeding (UGIB) - Kalula, Sebastiana Zimba (Centre for Infectious Disease Epidemiology and Research (CIDER), 2018)
Background and literature review: Introduction: Acute upper gastrointestinal bleeding is a common cause of emergency hospital admission. It is also not uncommon in patients already in hospital. The bulk of severe morbidity and mortality occurs in patients with recurrent bleeding or significant comorbid illness. The use non-steroidal anti-inflammatory drugs (NSAID), which is more common in the elderly, more than doubles the mortality associated with peptic ulcer complications. Endoscopy and endotherapy have improved outcome in patients with continued or recurrent bleeding. Clinical Predictors of Outcome: Despite improved technology in the management of upper gastrointestinal bleeding (UGIB), mortality has remained high. This has been attributed to the increase in the population of elderly people who tend to have other underlying diseases leading to the high mortality rate. From international literature, mortality varies from 4-10%. Most of the reports reflect mortality around 8%. A local retrospective study by Van Stiegmann et. al. (1983) on patients with bleeding peptic ulcer had an overall mortality of 5.4 %, and mortality of 9.8% in those treated surgically. Ideally to avoid waste of resources and time, emergency endoscopy should primarily be considered in relatively few patients at risk of further haemorrhage. In this class of patients, endoscopy is used not only for diagnosis but also for endoscopic treatment to control massive ulcer bleeding. This approach is worthy of consideration in a "resource poor" environment. Most previous studies have employed endoscopic criteria for identifying patients at high risk of poor outcome. These data are not available at the time of admission. This is therefore not helpful in the triage of patients prior to endoscopy. Groote Schuur Hospital (location for the current study) has experienced a significant staff cutback over the past 5 years. Few of our regional hospitals and none of our primary health care facilities have endoscopy facilities and endoscopic expertise is similarly limited. Given the pressures on the limited endoscopy services, there is a need for guidelines for the referral of patients to centres with these facilities. There is a possibility that the number of potential referrals of patients with upper gastrointestinal bleeding (UGIB) will increase as the primary health care services improve, a rational review of criteria for referral appeared timely. There would be need to triage patients into: i). those who must have endoscopy urgently and ii). those who could be safely referred for elective endoscopy. Most previous studies have looked at predictors of adverse outcome. To our knowledge no study has been done in South Africa to determine clinical predictors of good outcome prior to endoscopy, that would help determine patients who would recover uneventfully without urgent endoscopy. Study Rationale: Given the scarcity of both endoscopy resources and of information for the triage of patients who would recover uneventfully following UGIB without urgent endoscopy in our setting, this study set out to answer the question: Is it possible to identify clinical criteria that will predict patients with UGIB in whom endoscopy could be safely deferred? OBJECTIVES: 1. To identify clinical criteria that predict uneventful recovery. 2. To determine the accuracy of individual symptoms and signs or combinations. of symptoms or signs at the time of presentation in predicting uneventful recovery. Study population and Methods: Study design and study setting: The design was a prospective, descriptive, cross sectional study with an analytical component. The study was conducted at Groote Schuur Hospital (GSH), which is a tertiary referral teaching hospital with 14 70 beds. It is affiliated to the University of Cape Town.